1989
DOI: 10.1007/bf00199914
|View full text |Cite
|
Sign up to set email alerts
|

Production of cytokines after lipopolysaccharide stimulation of murine spleen cells during lymphoma development in AKR mice

Abstract: Injection of syngeneic lymphoma cells in AKR mice, resulted in an important increase of splenic natural killer (NK) activity in the early days following the graft. Modifications of the production of different types of cytokine: interferon, interleukins 1 and 2, tumor necrosis factor (IFN, IL-1, IL-2, TNF), involved in the regulation of NK activity, were investigated in short-term cultures of total, adherent and non-adherent fractionated spleen cells, using lipopolysaccharide as the triggering or amplifying age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Numerous reports claim that the mechanism of activation of cytotoxic activity by LPS implies IFN production [8,25]. In fact, LPS induces the production of various types of IFN [2,27,28,35]. In the experiments described we observed that of the IFN induced by LPS, about 80% is the "/type and 20% the a/~3 type.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Numerous reports claim that the mechanism of activation of cytotoxic activity by LPS implies IFN production [8,25]. In fact, LPS induces the production of various types of IFN [2,27,28,35]. In the experiments described we observed that of the IFN induced by LPS, about 80% is the "/type and 20% the a/~3 type.…”
Section: Discussionmentioning
confidence: 86%
“…Lipopolysaccharide (LPS) is an inducer of cytotoxic activity either after i.v. injection into mice [6] or in short-term culture [2]; it is known as an initiator of IFN [27,2,28,35] and prostaglandins [7,21], which regulate NK activity [30,36].…”
Section: Introductionmentioning
confidence: 99%